The Relationship of Antiphospholipid Antibodies to Thromboembolic Disease in Systemic Lupus Erythematosus: A Cross-Sectional Study - Long, A A; Ginsberg, J S; Brill-Edwards, P; Johnston, M; Turner, C; Denburg, J A; Bensen, W G; Cividino, A; Andrew, M; Hirsh, J (Thrombosis and Haemostasis, 1991)
In order to determine whether an association exists between antiphospholipid antibodies (APLA) and thromboembolic events in patients with systemic lupus erythematosus (SLE), we performed a cross-sectional study of consecutive unselected SLE patients. The occurrence of previous thromboembolic events was determined by investigators blinded to the APLA status of the patients by critical review of objective tests that had been performed at the time of symptomatic presentation and by performing venous Doppler ultrasound of the legs to elicit venous reflux as an indication of previous venous thrombosis. The presence of APLA was determined by coagulation assays for the lupus anticoagulant (LA) using five tests with well-defined control ranges and by ELISA assay for anticardiolipin antibodies (ACLA). These tests were measured on two separate occasions. The results of the study demonstrate a statistically significant association between persistently abnormal ACLA assays and thromboembolic events and a non-significant trend between persistently abnormal LA and thromboembolic events. Transient abnormalities of LA and ACLA were less strongly associated with thromboembolic events. We conclude that in patients with SLE, there is a significant association between thromboembolism and APLA.